2021
DOI: 10.1088/1742-6596/2094/4/042070
|View full text |Cite
|
Sign up to set email alerts
|

Development of technology for obtaining starch gluing modified with uzkhitan and hydrolyzed emulsion

Abstract: In this article, in order to reduce the consumption of starch for gluing warp threads and reduce the cost of sizing materials used in sizing and improve the quality of threads, an effective gluing composition was created based on a hydrolyzed acrylic emulsion (GAE) and uzkhitan (chitosan and carboxymethyl cellulose), that is, corn starch polymer and studied their rheological properties. In the article, the main threads passing through the gluing process and moving at a certain speed, which are then impregnated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…The main recommendations of the fabric structure are the linear density (diameter) of the yarn, the body and back yarns, the structure and application phase of the body and back density in the fabric, the filling and replenishment parameters, the fabric thickness, the base surface. These descriptions can be conditionally divided into two groupsfree and compulsory [3].…”
Section: Methodsmentioning
confidence: 99%
“…The main recommendations of the fabric structure are the linear density (diameter) of the yarn, the body and back yarns, the structure and application phase of the body and back density in the fabric, the filling and replenishment parameters, the fabric thickness, the base surface. These descriptions can be conditionally divided into two groupsfree and compulsory [3].…”
Section: Methodsmentioning
confidence: 99%
“…A number of scientists have studied the effect of the structure of cotton yarns on their abrasion resistance, and found that the effect of weaving on durability is mainly due to changes in waveforms, especially the radius of curvature of the yarn on the fabric surface. The bending radius increases with the elongation of the coatings, resulting in an increase in the amount of fibers that are prone to corrosion and, consequently, in the amount of yarn consumed [4].…”
Section: Modern Innovations Systems and Technologies 2022 2(1) ______...mentioning
confidence: 99%
“…As research methods, qualimetry methods are used, consistently implementing a complex algorithm for determining quality indicators [10,11].…”
Section: современные инновации системы и технологии // Modern Systems...mentioning
confidence: 99%